IMPLIKASI APLIKASI BUJANG KURIR TERHADAP PERTUMBUHAN EKONOMI DI KOTA PONTIANAK - NIM. A1012201130, DAHLIYA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract Globalization, advances in science and technology and information have resulted in countries in the world appearing to be without borders. Various developments in knowledge and technology in a country will quickly spread and be easily accessed by people in other parts of the world.The government's role in encouraging the implementation of intellectual property rights in the bujang courier application in increasing economic growth in Pontianak City. To find out the role of the government in encouraging the implementation of intellectual property rights in the Bujang Courier application in increasing economic growth in Pontianak City. It is hoped that being able to ensure proper IPR protection, the